Maternal nutrient intakes and levels of energy underreporting during early pregnancy - McGowan, C A; McAuliffe, F M (European journal of clinical nutrition, 2012)
Background/Objectives: Pregnancy is a critical period in a woman's life where nutrition is of key importance for optimal pregnancy outcome. The aim of this study was to assess maternal nutrient intakes during early pregnancy and to examine potential levels of energy underreporting. Subjects/Methods: Three-day food diaries were collected from 260 healthy pregnant women sampled from the control arm of a large Irish pregnancy cohort at 14 weeks gestation (range 12–20 weeks). Results: Up to 45% of pregnant women may be underreporting daily energy intake (EI). Multiple logistic regression analysis found that having a body mass index (BMI) of ⩾25 kg/m 2 compared with a BMI <25 kg/m 2 (odds ratio, 4.4; 95% confidence interval, 2.5–7.7) was the main predictor of energy underreporting. Educational attainment is also an important predictor of energy underreporting. Women who underreport their EI tend to be less compliant with the current dietary recommendations for pregnancy. Conclusions: These data highlight the need for more education and public health interventions among pregnant women to achieve current dietary guidelines. In the analysis of dietary intakes, removal of extreme under reporters (Goldberg's ratio <0.9) may allow for more accurate assessment of nutritional intakes amongst pregnant women.